Applied sociology scientific school of full professor G. P. Davidyuk - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2023)
The article deals with the history of forming the scientific school of applied sociology by full professor G. P. Davidyuk. His great personal contribution to the revival of sociological science and the institutionalisation of sociological education in Belarus is noted. He created the first scientific structures of a sociological profile in Belarus. He wrote the first textbooks «Fundamentals of applied sociology» (1975) and «Applied sociology» (1979), under his scientific supervision the country’s first «Dictionary of applied sociology» (1984) was prepared. There were created the conditions and was made an attempt to train professional sociologists and personnel of the highest scientific qualification at the Belarusian State University. The Problematic Research Laboratory of Sociological Research of the Belarusian State University in the 1970–80s has become a leading scientific centre in the country under his leadership. Sociological structures were created in the leading universities of the republic, following its example. G. P. Davidyuk represented Soviet and Belarusian sociology at international forums. The activities of the sector of applied sociology at the Belarusian State University gave impetus to the development of industrial sociology.
Keywords: G. P. Davidyuk; the revival of sociology; scientific school; applied sociology; the first textbooks of sociology; work «Dictionary of applied sociology»; factory sociology